The Influence of Socio-Psychological Factors on Readiness to Become a Warrantor in the Situation of the Institutional Borrowing - Анастасия Юрьевна Алексеева (Journal of Economic Sociology, 2010)
The first part of the paper is devoted to the theoretical interpretation of guarantee as form of trustworthy action. The main focus is given to the determination of the factors (socio-cultural, institutional and socio-psychological), which may impact the individual decision about the guarantee. The main idea of the survey is that the decision to become a warrantor is influenced by the situational conditions (for example, the assessment of trust to the contractor, past experience, objective conditions and etc.), as well as by individual’s own resources that characterize the peculiarities of perception of his/her own social position. The purpose of this paper is to analyze the impact of socio-psychological capital of potential warrantor (social optimism, security feeling and etc.) on the readiness to act trustfully. Relying on the theoretical conceptions stated in the first part the secondary data analysis was done. The data was collected from the Novosibirsk monitoring poll.